Da relação de parentesco colateral na família recomposta - Maia, Renato (2007)
The following paper deal related to the evolution of familial organization and also the format of step family, in order to show that the relationship among relatives is far beyond the blood or the disposition of the law. The legal ties of kinship is praiseworthy in what concerns its changes along the history, focusing on the answers to the anxiety of a Culture of certain time or by establishing the dignity of members from a helpful family, such a way this one could survive in spite of steady social changes. This present writing looks at a probable organization carefully in order to establish relationships among adopted brothers. The presented study analyses the unexpected kinships within a decomposed family. The blood, civil and affinity kinships towards the disposition of the Article 1.595 from Civil Code, and the distinction between kinship and affinity, once it is present in. The analysis is made from the social affection paternity that s going to be performed by the couple according to its previous spouse s son; mainly by the legal or biological absence. This research follows the principle of de lege ferenda such a way the recomposed family s institutional and juridical recognition provides the kinship establishment among real brothers, in obedience to the scientific thesis, considering this writing is useful to obtain the Title of Doctor . It still suggests the study of the recomposed family structure in agreement with compared Civil Law, mainly related to German, Argentinean and Brazilian legislations